A loaded self-managed exercise programme for patellofemoral pain: a mixed methods feasibility study - Smith, Benjamin E. (2019)
Patellofemoral pain (PFP) is a common musculoskeletal disorder, with one in five young adults suffering at any one time. The main symptoms include pain behind or around the patella (kneecap) during activities that load the joint, such as climbing stairs and exercise.